Zmiany i projekty zmian w polskim systemie wyborczym po uchwaleniu Kodeksu wyborczego (Politeja, 2016)
Polish electoral system in the process of changeThe article is the critical examination of changes in the polish electoral system after codification in 2011 year. Author analyses all changes in electoral law since 5 January 2011 and all draft bills which have been submitted to the Marshall of the Sejm in two last terms. The most important aims of the article are the answers the questions about reasons, premises and purposes of the changes and draft bills. Author also identify three types of changes in electoral system – adjustments, reforms and modernizations – and tries to show basic threats and problems connected with changes in electoral law.